2022
DOI: 10.1038/s41598-021-03313-9
|View full text |Cite
|
Sign up to set email alerts
|

Induced magnetic field and viscous dissipation on flows of two immiscible fluids in a rectangular channel

Abstract: The unsteady, magneto-hydrodynamic generalized Couette flows of two immiscible fluids in a rectangular channel with isothermal walls under the influence of an inclined magnetic field and an axial electric field have been investigated. Both fluids are considered electrically conducting and the solid boundaries are electrically insulated. Approximate analytical solutions for the velocity, induced magnetic, and temperature fields have been determined using the Laplace transform method along with the numerical Ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These facts provoked the academics Seth and Singh [31], Singh et al [32] and Singh and Kolasani [33] to explore the wall electrical conductivity and energy dissipation effects to the hydromagnetic channel flows under the diverse geometrical flow formations. Some noteworthy research works including the energy dissipative effects are owed to Gopal et al [34], Atif et al [35], Poddar et al [36] and Shah et al [37]. The significance of motional induction and Hall current phenomena on hydromagnetic flows are clearly visible when the fluid is highly electrically conducting and the strength of the imposed magnetic field is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts provoked the academics Seth and Singh [31], Singh et al [32] and Singh and Kolasani [33] to explore the wall electrical conductivity and energy dissipation effects to the hydromagnetic channel flows under the diverse geometrical flow formations. Some noteworthy research works including the energy dissipative effects are owed to Gopal et al [34], Atif et al [35], Poddar et al [36] and Shah et al [37]. The significance of motional induction and Hall current phenomena on hydromagnetic flows are clearly visible when the fluid is highly electrically conducting and the strength of the imposed magnetic field is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
“…[36] and Shah et al. [37]. The significance of motional induction and Hall current phenomena on hydromagnetic flows are clearly visible when the fluid is highly electrically conducting and the strength of the imposed magnetic field is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al [23] examined two-phase Couette flow in a channel subjected to a magnetic field. Yadav and Kumar [24] conducted a study on the entropy generation of two immiscible fluids in a conduit.…”
Section: Introductionmentioning
confidence: 99%
“…Radiated nanomaterial flow of MHD fluid with the geometry of curved surface with second order slip is scrutinized by Muhammad et al 19 . Relation between viscous dissipation and induced magnetic field over the rectangular channel is comprehensively discussed by Shah et al 27 . Ishfaq et al 28 probed the nanofluid moving subjected to an expandable surface underneath the consequence of boundary layer approximation and found that the temperature field amplifies owing to an enlargement in volumetric fractional size of nano molecules.…”
Section: Introductionmentioning
confidence: 99%